SPERMATOGENESIS AND SPERM BUNDLE FORMATION IN THE DRAGON FLY ANAX GUTTATUS (BURMEISTER) (INSECTA: ODONATA: AESHNIDAE) - S. S. BAKARE; R. J. ANDREW (The Bioscan, 2011)
In Anax guttatus, the freshly moulted adults contain primary spermatogonia to fully-formed spermatozoa indicating commencement of spermatogenesis in the ultimate nymphal stage. All the progametes of a single cyst exhibit a single stage of spermatogenesis. Vigorous process of spermiogenesis occurs in the adult dragonfly, leading to the formation of spermatozoa and sperm bundle. The “shuttle cock” shaped sperm bundles are formed with a conical head cap. The central canal secretes thick viscous seminal fluid around the sperm bundle which facilitates downward migration of sperm bundles from the central canal to the vas deferens. In mature adults, the vasa deferentia, seminal vesicles and sperm sac are completely packed with the sperm bundle embedded in viscous seminal fluid secreted by epithelial cells of the genital ducts. The acellular wall of cyst containing mature spermatozoa undergoes ultrastructural changes which help the sperm bundle to move towards the central canal.